2023
DOI: 10.1002/ffj.3743
|View full text |Cite
|
Sign up to set email alerts
|

Ortho‐ and Retronasal stimulations with specific food odours: Hedonic and familiarity ratings are related to chemosensory pleasure scale (CPS) scores

Abstract: Volatile compounds can reach olfactory epithelium though the nose (orthonasal olfaction) or the mouth (retronasal olfaction). Although differences have been found between these two pathways in terms of odour sensitivity and identification, few studies have examined ortho‐ and retronasal differences taking into consideration the three main dimensions of olfactory perception (i.e. hedonicity, intensity and familiarity). Olfactory perception, and particularly odour hedonic perception, is influenced by several fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Furthermore, some authors show no significant difference between the two pathways for lavender, chocolate, farnesol, and butanol odors (Hummel & Heilmann, 2008; Small et al, 2005). Recently, no difference in odor hedonic ratings was found between ortho- and retronasal routes for nine food odors (Bontempi et al, 2023). However, the results of this study showed differences when considering the total score of the Chemosensory Pleasure Scale (Zhao et al, 2019): Participants with a high total score on the Chemosensory Pleasure Scale rated food odors as more pleasant than those with a low total score, and this difference was significant for retronasal stimulation.…”
Section: Variability In Odor Hedonic Perception In Relation To Stimul...mentioning
confidence: 99%
“…Furthermore, some authors show no significant difference between the two pathways for lavender, chocolate, farnesol, and butanol odors (Hummel & Heilmann, 2008; Small et al, 2005). Recently, no difference in odor hedonic ratings was found between ortho- and retronasal routes for nine food odors (Bontempi et al, 2023). However, the results of this study showed differences when considering the total score of the Chemosensory Pleasure Scale (Zhao et al, 2019): Participants with a high total score on the Chemosensory Pleasure Scale rated food odors as more pleasant than those with a low total score, and this difference was significant for retronasal stimulation.…”
Section: Variability In Odor Hedonic Perception In Relation To Stimul...mentioning
confidence: 99%
“…Both orthonasal and retronasal olfaction are essential for human sensory experience, as they enable the perception of a wide range of aromatic compounds that influence the hedonic and cognitive evaluation of the sensory qualities of various substances. 32,33 The human olfactory system has an impressive ability to detect and recognize odors at extremely low concentrations. Certain potent odorants may be easily identified by the human nose even at parts per billion (ppb) or parts per trillion (ppt) levels.…”
Section: ■ Human Perception Of Odorsmentioning
confidence: 99%
“…Factors such as age, gender, genetics, exposure history, and personal experiences can influence an individual's sensory threshold. 32,33 Understanding human perception of odors provides the foundation for advanced analytical techniques such as GC-O analysis.…”
Section: ■ Human Perception Of Odorsmentioning
confidence: 99%
See 2 more Smart Citations